AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI KECAMATAN SAPARUA KABUPATEN MALUKU TENGAH - Zacharias, Tihubijuluw; Iskandar, Andri (JURNAL BADATI, 2025)
This study aims to analyze the accountability of village fund allocation management in Saparua District, Central Maluku Regency. The research approach used is a qualitative approach. The informants of this study are officials who contribute to the management of Village Fund Allocation in Saparua District, Central Maluku Regency. In addition, the author conducted in-depth interviews with key informants, namely community leaders. The researcher used an interactive analysis model from Miles Huberman by conducting data reduction, data presentation and drawing conclusions. The results of the study concluded that planning, implementation, accountability, administration to reporting the use of ADD in Saparua District were carried out through the Village Deliberation process and community supervision, which guaranteed transparency, efficiency, and accountability in fund management. This process strengthens community trust in the village government, ensures that ADD is used according to regulations for village welfare, and supports the sustainability of the ADD program in the future. Accountable administration and timely reporting are key to building public trust in the use of village funds.